ANALYSIS OF FINANCIAL STATEMENTS USING TREND ANALYSIS METHOD AS A BASIS FOR ASSESSING THE CONDITION OF PT ASTRA COMPANY INTERNATIONAL TBK. PERIOD 2020-2022 - YOANDA PUTRA; Ridho Adeansyah; Muhamad Akbar; Selvin Thean Valentina; Suci Fitria Ramadani; Yunsri Putri (MANKEU (JURNAL MANAJEMEN KEUANGAN), 2024)
This research was conducted at PT. Astra International Tbk. seen from the financial balance report for the 2020-2022 period from data sources on the Indonesian stock exchange. The purpose of this study is to determine the condition of the financial statements and the condition of the company. The research method used is a quantitative descriptive method with secondary data sources. The technique of data collection used is the percentage, which is generated by using the trend method analysis and tends to increase. The results of the balance sheet report that have been studied show that the asset section for the 2020-2021 period has increased by 8%, and in the 2021-2022 period, it has also increased, although not significantly compared to the previous year of 4%. In the liability section for the 2020-2021 period, there has been a significant increase amount 36%, and in the 2021-2022 period also an increase, although not too significant, by 18%. And on the part of equity, the 2020-2021 period has increased by 10%, and in the 2021-2022 period, there has been a quite significant increase of 23%.